Application of Blended Learning Models in Logic and Mathematical Reasoning Courses - Zamzam, Aliya; Diniyah, Syamsyiatud; Fikri, Muhammad (Etunas Sukses Sistem, 2022)
The purpose of this study was to determine the application of the blended learning model in logic and mathematical reasoning courses. Pre-test in groups-Post-test research The design of the application of the experimental method is in the form of a pre-experimental research design. The population of this study were students in the mathematics education subjects of University x, logic and mathematical reasoning. The samples in this study were Morning Class A students in the subjects of Logical and Mathematical Reasoning. This instrument consists of several tests of logical and mathematical reasoning questions. The results showed that the application of the mixed learning model to mathematics and logic material increased student achievement. Student achievement before being given the blended learning model is low. The student's score after receiving the blended learning model is considered good.